Nanoformulated herbal compounds: enhanced antibacterial efficacy of camphor and thymol-loaded nanogels - Abbas Abdollahi; Narges Fereydouni; Hamid Moradi; Abolfazl Karimivaselabadi; Elham Zarenezhad; Mahmoud Osanloo (BMC, 2024)
Abstract Herbal components are highly useful assets for the advancement of novel antibacterial drugs. Nanotechnology holds great promise as an approach to enhance the effectiveness and develop the composition of these substances. The study developed nanogels incorporating camphor, thymol, and a combination derived from the initial nanoemulsions with particle sizes of 103, 85, and 135 nm, respectively. The viscosity of nanogels and the successful loading of compounds in them were examined by viscometery and ATR-FTIR studies. The bactericidal properties of the nanogels were examined against four bacterial strains. The nanogel containing camphor and thymol at 1250 µg/mL concentration exhibited complete growth suppression against Pseudomonas aeruginosa and Staphylococcus aureus. The thymol nanogel at 1250 µg/mL and the camphor nanogel at 2500 µg/mL exhibited complete inhibition of growth on Listeria monocytogenes and Escherichia coli, respectively. Both nanogels showed favorable effectiveness as antibacterial agents and could potentially examine a wide range of pathogens and in vivo studies.